Research on Market Dynamics and Corporate Motivations: Insights from Stock Split Phenomenon - Yan, Shangyu (Transactions on Economics, Business and Management Research, 2024)
This study focuses on the phenomenon of stock splits, with a primary aim to address three pivotal questions: 1. What are the valuation implications of stock splitting? 2. Which determinants influence market reactions to announcements of stock splits? 3. What characteristics drive the decision to enact a stock split? Through meticulous examination of relevant literature and analysis of provided data, this paper presents several key findings. Firstly, it is observed that the market demonstrates a significant reaction within the [0, 1] day window surrounding a stock split announcement, whereas no discernible effect is noted beyond this interval, as evidenced by cumulative abnormal returns. Secondly, the degree of market response is found to be modulated by factors such as post-announcement return on price adjustment (LPRCAFT), company size, historical performance (PASTPERF), and adjustments in dividend payouts (DIVUP). Lastly, the inclination towards executing a stock split is predominantly influenced by the company’s recovery performance, its share price, and the overall size of the company.